Perfonnance of national innovation systems during the global crisis: a cross-country analysis - Kazazoğlu, Gözde Nur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
After the 2007 financial crisis and with the rise of information and communication technologies, the main driver of sustainable growth shifted from capital accumulation toinnovation driven and knowledge based economy. Tllis focus on knowledge and innovation driven countries and regions to constitute innovation strategies and plans in order to use scarce resources efficiently and maximize the value added by innovation to economic and social welfare. fn this study, two alternative models with two different approaches of Data Envelopment Analysis (DEA) under two different specifications (input-oriented and output-oriented) are utilized to trace innovation performance across 58 countries during the global crisis from 2007 to 2012. The empirical evidence reveals that the negative effects of2008 crisis are reflected on innovation efficiencies of countries in 2008 in the base model and 2009 in the lag model. In addition, grouping countries according to their ODP and GDP per capita and implementing two different models show that there could be differences in the innovation efficiency results since the DEA model shows the innovation efficiency in comparison with the other countries' efficiency. Lastly, with the data it is proven that higher GDP or higher GDP per capita do not lead to hjgh innovation efficiency.
Keywords: Global Financial Crisis, 2008-2009.; International finance.; Innovation -- Management.